Effect of Heat Treatment on the Microstructure and Mechanical Properties of Inconel 718. (2018) - Anbarasan, N.; Gupta, Bikash Kumar; Prakash, S.; Muthukumar, P.; Oyyaravelu, R.; Kumar, R. John Felix; Jerome, S.
Abstract: The welding of Inconel 718 is considerably difficult due to the formation of heat affected zone (HAZ) microfissuring and there are many factors such as elemental segregation, grain size and secondary phase distribution influence microfissuring. The effect of the above-mentioned factors can be controlled by the suitable heat treatment. In this study, an attempt has been made to understand the effect of heat treatment on the microfissuring. Inconel 718 sheets were solutionized at 980 °C and 1066 °C for the period of 1 hour soaking used were subsequently cooled by furnace cooling (FC) and iced brine quenching (ICE). The microstructural observation revealed the grain size increase in sample subjected to 1066°C heat treatment. SEM & EDS results showed more segregation of Nb around grain boundaries in 1066°C heat treated samples. Nevertheless, there is an increase in hardness of FC samples due to evolution of γ′ and γ′′ precipitates which were confirmed from X-Ray diffraction results.